2022
DOI: 10.3389/fvets.2022.904786
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Investigation of 100 Cases of Abortion in Sheep in Uruguay: 2015–2021

Abstract: The aim of this work was to identify causes of abortion through laboratory investigations in sheep flocks in Uruguay. One hundred cases of abortion, comprising 58 fetuses, 36 fetuses with their placentas, and 6 placentas were investigated in 2015–2021. Cases were subjected to gross and microscopic pathologic examinations, and microbiological and serological testing for the identification of causes of abortion, including protozoal, bacterial, and viral pathogens. An etiologic diagnosis was determined in 46 (46%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 96 publications
1
4
0
1
Order By: Relevance
“…Unfortunately, an etiological causative agent could not be identified in the majority of abortion cases in this study. This is in complete agreement with previous reports where it was suggested that less than 50% of abortion causes could have been identified using the best diagnostic capabilities ( Dorsch et al , 2022 ). This fact could be explained by a lack of case definition, contaminated or improper sample collection, or transport.…”
Section: Discussionsupporting
confidence: 93%
“…Unfortunately, an etiological causative agent could not be identified in the majority of abortion cases in this study. This is in complete agreement with previous reports where it was suggested that less than 50% of abortion causes could have been identified using the best diagnostic capabilities ( Dorsch et al , 2022 ). This fact could be explained by a lack of case definition, contaminated or improper sample collection, or transport.…”
Section: Discussionsupporting
confidence: 93%
“…The selection performed in this study of the most frequent abortifacient pathogens associated with small domestic ruminants in Europe allowed us to detect pathogens involved in abortions in around 75% of cases, higher rates than most of previous case studies ( 23 25 ). In contrast, no agent could be detected in about a quarter of the cases, which may either be associated with non-infectious agents, such as toxics, nutritional disorders, genetic diseases, stress or extreme climatic conditions ( 26 , 27 ) or, to a lesser extent, less frequent pathogens that may cause abortions secondarily ( 8 , 13 ).…”
Section: Discussionmentioning
confidence: 96%
“…The presence of leptospires in those different sites highlights that several organs should be collected simultaneously for diagnosis, beyond the kidney and liver. When available, molecular analysis of the placenta has been encouraged as well [ 10 , 14 , 38 ]. Unfortunately, in the present study, placentas were not available for testing.…”
Section: Discussionmentioning
confidence: 99%